2016
DOI: 10.1155/2016/3162595
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Short- and Long-Term Therapeutic Outcomes of Infliximab- versus Tacrolimus-Based Strategies for Steroid-Refractory Ulcerative Colitis

Abstract: Background/Aims. Antitumor necrosis factor antibodies and calcineurin inhibitors have shown good therapeutic efficacy for steroid-refractory ulcerative colitis (UC). Although some studies have compared the efficacy of infliximab (IFX) and cyclosporin A, there are no published studies comparing IFX and tacrolimus (Tac). This study aimed to compare therapeutic efficacies between IFX- and Tac-based strategies for steroid-refractory UC. Methods. Between July 2009 and August 2013, 95 patients with steroid-refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 32 publications
(35 reference statements)
3
48
0
Order By: Relevance
“…They reported CRP levels at baseline were not statistically different between groups, but serum albumin levels were not discussed. Endo et al [10] reported the clinical remission rate after 2 months was 68.8% and 55.3% in the IFX and Tac groups, respectively, in their retrospective study of 95 patients with steroid-refractory UC. They reported that serum albumin and CRP levels at baseline were significantly different between groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported CRP levels at baseline were not statistically different between groups, but serum albumin levels were not discussed. Endo et al [10] reported the clinical remission rate after 2 months was 68.8% and 55.3% in the IFX and Tac groups, respectively, in their retrospective study of 95 patients with steroid-refractory UC. They reported that serum albumin and CRP levels at baseline were significantly different between groups.…”
Section: Discussionmentioning
confidence: 98%
“…Tacrolimus (Tac), a calcineurin inhibitor that has a mechanism of action similar to CsA, also has therapeutic efficacy for moderate to severe UC [7,8]. Several retrospective studies showed IFX and Tac had equal efficacy for moderate to severe UC [9][10][11]. These studies were retrospective and therefore the background characteristics of the patients were not randomized.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flow diagram which describes the reasons for citations exclusion. Finally, 22 studies (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)28,30,32,33) that fulfilled eligibility criteria were included. Only two studies were randomized controlled trials (24,25) (Ogata 2006 and Ogata 2012); these were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mild clinical symptoms such as tremor and paraesthesia were frequently observed in patients treated with TAC [7][8][9][10]. Renal dysfunction was also observed in the TAC group; however, creatinine levels returned to the normal range after reducing the dose of TAC [9].…”
Section: Safety and Adverse Eventsmentioning
confidence: 98%
“…Four studies [7][8][9][10] assessed the safety and adverse events of TAC and IFX, and the other study [11] did not.…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%